Comparing different sperm concentrations for optimizing cooled semen use in the dog - Sugai, Nicole; Werre, Stephen; Cecere, Julie T.; Balogh, Orsolya (Frontiers in Veterinary Science, 2024)
The use of shipping canine semen for artificial insemination has bloomed over the last 20 years. This allows for the spread of genetic material while overcoming geographical or time-related challenges. The optimal sperm concentration for cooled semen transport in the dog is unknown. Often canine semen is extended 1:3–5 vol:vol without standardized sperm concentrations for cooled shipment. We compared different sperm concentrations for cooled storage and hypothesized that lower concentrations would result in better semen quality. Semen was collected from healthy client-owned dogs (n = 8). Individual ejaculates were divided into a control aliquot (CON) extended 1:3 vol:vol with a commercial extender. The remaining sample was centrifuged and extended to 200 ×106 sperm/ml (C200), then serially diluted to 100, 50, and 25 ×106 sperm/ml concentrations (C100-C25). Aliquots were cooled for 24 h and then centrifuged and re-extended. Sperm concentration, plasma membrane integrity (PMI, %), motility (subjective total, STM; computer-assisted sperm analysis (CASA) total and progressive, TM, PM; %), and normal morphology (NM, %) were assessed in raw semen (T0), post-extension (T1), after 24 h of cooling (T2), and after processing at 24 h (T3). Cooling resulted in significant declines in STM and NM for all groups and in decreased PMI for CON and C25-50. After cooling (at T2), PMI was significantly lower for C25 compared with all the groups and higher for CON compared with C25-100 (p ≤ 0.038). Processing and re-extension after cooling further decreased the spermiogram parameters. At T3, PMI for CON was similar to C200 but significantly higher than C25-100, while C25 had the lowest PMI. For motility parameters and NM, C25 performed worse than all or most of the other groups. Comparing CON at T3 with C25-200 at T2, PMI, STM, and NM for CON were significantly lower than C25-200, C200, and C100-200, respectively. In conclusion, our results show that cooling canine semen for 24 h at 200 ×106 sperm/ml final concentration after processing or extending 1:3 vol:vol without centrifugation is preferred based on the highest PMI. If volume restrictions apply, processing raw semen and extending to the desired volume with higher sperm concentrations at the collection facility is superior to centrifugation and volume adjustment after 24 h of cooled storage.